Evidence of α-, β- and γ-HCH mixture aerobic degradation by the native actinobacteria Streptomyces sp. M7 - Sineli, Pedro Eugenio (2016)
The organochlorine insecticide γ-hexachlorocyclohexane (γ-HCH, lindane) and its non-insecticidal α- and β-isomers continue to pose serious environmental and health concerns, although their use has been restricted or completely banned for decades. In this study we report the first evidence of the growth ability of a Streptomyces strain in a mineral salt medium containing high doses of α- and β-HCH (16.6 mg l−1) as a carbon source. Degradation of HCH isomers by Streptomyces sp. M7 was investigated after 1, 4, and 7 days of incubation, determining chloride ion release, and residues in the supernatants by GC with µECD detection. The results show that both the α- and β-HCH isomers were effectively metabolized by Streptomyces sp. M7, with 80 and 78 % degradation respectively, after 7 days of incubation. Moreover, pentachlorocyclohexenes and tetrachlorocyclohexenes were detected as metabolites. In addition, the formation of possible persistent compounds such as chlorobenzenes and chlorophenols were studied by GC–MS, while no phenolic compounds were detected. In conclusion, we have demonstrated for the first time that Streptomyces sp. M7 can degrade α- and β-isomers individually or combined with γ-HCH and could be considered as a potential agent for bioremediation of environments contaminated by organochlorine isomers.